PENGARUH PENGEMBANGAN SDM TERHADAP KOMPETENSI KARYAWAN YANG BERDAMPAK PADA EFEKTIVITAS ORGANISASI DI INDUSTRI AIR MINUM - Dany Jaya Wardana; Rina Anindita; Agus Yulistiyono (JMB : Jurnal Manajemen dan Bisnis, 2022)
Drinking water is the livelihood of many people, therefore inorder to meet these needs, the drinking water management industry must be able to provide an excellent services in every aspect of quality, quantity and continuity. To achieve this goal, the organizational need a competent employees, so they could run the company effectively. Therefore, this study aims to examine the effect of human resource development programs that is training, talent management, and performance management on competencies that have an impact on organizational effectiveness in the drinking water management industry. The sampling method is purposive sampling, that have 252 sample of employees who work in drinking water management industry. This type of research is deductive with data collection by distributing questionnaires. The analytical method used is the Structural Equation Model (SEM). The results of these study conclude that there is an effect of training on competencies, there is an effect of talent management on competencies, there is an effect of performance management on competencies, and there is an effect of competent employees to an organizational effectiveness. The role of employee competence as a media variable has been proven to influence the role of training, talent management, and performance management to increase organizational effectiveness. The implication of this research is that a leaders should provide training and development to improve their employee competencies, so that they can increase organizational effectiveness in order to improve services to the community in terms of drinking water services